Characterization and rheological properties of Camelina sativa gum: interactions with xanthan gum, guar gum, and locust bean gum - Sanchez Gil, Yaritza M. (Kansas State University, 2014)
Gums are water-soluble polysaccharides used in many industrial and food applications because of their functions such as thickening, gelling, emulsification, adhesion, and encapsulation. Interactions between gums are conducted to enhance functional properties of finished products and reduce processing costs. In this study, camelina gum, from the oil-seed plant Camelina sativa, is characterized by carbohydrate composition and morphological, thermal, and rheological properties. Interactions with xanthan gum, galactomannans guar gum, and locust bean gum (LBG) are also studied. Camelina gum is composed of arabinose, rhamnose, galactose, glucose, xylose and mannose; according to high-performance anion exchange chromatography analysis. Scanning electron microscopy and transmission electron microscopy images showed camelina gum with fibrillar structure and intermeshed network. Camelina gum solutions exhibited a shear thinning flow behavior in a range of concentrations (0.1% to 2.0% w/w) and shear rate (0.001 sˉ¹ to 3000 sˉ¹). Camelina gum is temperature independent at temperature ranges from 4 °C to 90 °C. The apparent viscosity increased as gum concentration increased. Mechanical properties of camelina gum demonstrated viscoelastic behavior with entangled molecular chains. Interaction of camelina gum with monovalent salt NaCl significantly reduced the viscosity of camelina gum solution at 1% when NaCl concentration increased. Camelina gum is soluble in water up to 60% ethanol content, in which the rheological properties do not significantly differ from camelina gum in water solution only. A synergy with xanthan and galactomannans was determined. All mixtures exhibited shear-thinning flow behavior, solid-like behavior at low frequencies, and liquid-like behavior at high frequencies. For camelina-galactomannans mixtures, synergistic interactions occurred in LBG-camelina mixtures at ratios of 1:1 and 3:1. For xanthan-camelina mixture, maximum synergy was observed at the ratio 1:1. Synergistic effects of gum mixtures suggest dependency on the ratios and chemical structures of the gums. The effect of temperature on apparent viscosity of mixtures is not significant. Results showed that camelina gum can be used for commercial applications.
Keywords: Camelina; Gums; Rheology; Synergy; Mixtures; Composition